Evaluation and treatment of injury and illness in the ultramarathon athlete - Krabak, B. J.; Waite, B.; Lipman, G. (Physical Medicine & Rehabilitation Clinics of North America, 2014)
Participation in ultramarathon races and knowledge of these athletes continues to increase as the sport becomes more popular. Physicians and athletes need to better understand the impact of the unique aspects of ultramarathon races, such as race environment (temperature, humidity, and altitude), race distance, race stages, nutritional requirements and equipment, on athlete injuries and illness. Proper treatment of injuries and illnesses during an ultramarathon race is important for avoiding long-term medical issues. In this article, the evaluation and treatment of common musculoskeletal injuries and medical illnesses in ultramarathon runners are reviewed.